(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Asthma is an inflammatory airway disease, which is characteristic by wheezing, chest tightness, dyspnea and cough, all symptoms that are occupied with obstruction of respiratory airway. Aim: investigate guggulsterone activity on improve inflammatory events that associated with asthma. Method: 48 healthy rats (albino, male) divided to 6 groups, rats were sensitized with OVA and preparation lung tissue homogenate for measurement of inflammatory parameters by ELISA and RT-PCR. Also, preparation of lung tissue for histopathological examination. Results: All parameters are significant reduction in treated group with guggulsterone than sensitized group. Also, gugglsterone-treated group’s slides with less inflammatory signs compared to sensitized group slide. Conclusion: Guggulsterone improve inflammatory events that associated with asthma.